ANALISIS DISTRIBUSI DAN EFISIENSI PEMASARAN PUPUK ORGANIK KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU (Studi Kasus: CV. Riau Jaya Perdana Tambusai) - Arpan; Defidelwina; Kusmiati (SUNGKAI, 2026)
One of the companies engaged in the organic fertilizer industry is CV. Riau Jaya Perdana Tambusai which is located in Rokan Hulu Regency. CV. Riau Jaya Perdana Tambusai, established in 2020 in Desa Talikumain, Kecamatan Tambusai, Kabupaten Rokan Hulu, Riau, is an organic fertilizer distribution company that plays a role in supporting sustainable agriculture. As a developing company, its main challenge is to improve distribution and marketing efficiency to remain competitive in the market. Therefore, the company needs to optimize operational costs and expand its marketing network. Based on this, this study aims to analyze the distribution of organic fertilizer marketing at CV. Riau Jaya Perdana Tambusai and assess its efficiency level. This research adopts a case study approach with descriptive analysis to explain the organic fertilizer marketing distribution patterns at CV. Riau Jaya Perdana Tambusai. Marketing efficiency is analyzed using cost calculation formulas, marketing margins, and farmer share to determine the extent to which organic fertilizer distribution operates efficiently. The findings indicate that the company employs three distribution patterns: zero-level (direct purchase by consumers from CV), level I (through distributors), and level II (involving agents and distributors). The analysis shows a marketing efficiency rate of 2%, classified as efficient (<50%), particularly in level I, despite incurring fuel costs. Meanwhile, level II proves to be more efficient as it does not require additional marketing costs.